Сравнительный анализ 2D И 3D моделей турбулентной естественной конвекции и теплового поверхностного излучения в замкнутых областях - Мирошниченко, Игорь Валерьевич (Перспективы развития фундаментальных наук. Т. 3 : сборник научных трудов XV Международной конференции студентов, аспирантов и молодых ученых, 24-27 апреля 2018 г.)
Turbulent natural convection with surface thermal radiation in air-filled enclosures has been investigated. The equations of conservation of mass, momentum and energy are solved using both finite difference and control volume methods. It should be noted that the working medium is Newtonian and heat conducting fluid, where the Boussinesq approximation is valid. The walls are supposed to be gray, diffuse emitters and reflectors of radiation. The left and right surfaces of the enclosure are isothermal walls, while other surfaces are adiabatic walls. The considered fluid flow is turbulent. The main aim of the present research is to compare the heat transfer process in 2D and 3D enclosures. Detailed results including flow profiles, temperature fields, and average Nusselt numbers have been presented.